Experimental Investigation of a Self-Healing Concrete Considering Bacillus Megaterium Bacteria and Fibres - Bhargava, Vandana; Sharma, Akhilesh; Gupta, Sandeep (International Journal of Scientific Research in Civil Engineering, 2022)
It is strong enough to resist compressive load but prone to cracking due to weak in tension which ultimately reduce the life of structure. Hence, any effort to improve the life span of structure will indirectly improve the sustainability of the environment. Cracks in concrete lead to ingress of chemicals in to concrete structure resulting in lower strength and durability. To increase the durability of the structure either cracks are repaired which is expensive or provide extra reinforcement to ensure the cracks width stays within certain limit. Only for durability reason, this extra steel is not desirable. One way to increase the durability of structure and reduce such extra cost is to use self-healing concrete. Self- healing of concrete is any process by the material itself involving the recovery and hence improvement of performance after an earlier action that had reduce the performance of material. In this study we are mixing Bacillus Megaterium bacteria with fibers in concrete with the motive to enhance its self healing properties with strengthening. Here it is concluded that with bacteria concrete become more resisting to weathering effect and have capability to self heal with addition of fibers become comparatively more durable and load bearing.